2007
DOI: 10.1016/j.bandc.2006.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder and emotion regulation: Insights from the Polyvagal Theory

Abstract: The current study provides the first published evidence that the parasympathetic component of the autonomic nervous system differentiates the response profiles between individuals diagnosed with borderline personality disorder (BPD) and controls. Respiratory sinus arrhythmia (RSA), a non-invasive marker of the influence of the myelinated vagal fibers on the heart, and heart period were collected during the presentation of film clips of varying emotional content. The BPD and control groups had similar initial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 40 publications
6
116
2
3
Order By: Relevance
“…This work is consistent with other findings using heart rate measures [66], which found that individuals with BPD demonstrate less parasympathetic activity in response to emotional films. Greater parasympathetic activity promotes social engagement, whereas less is more indicative of preparedness for fight/flight.…”
Section: Disturbed Controlled and Reflective Processes In Borderlinesupporting
confidence: 93%
“…This work is consistent with other findings using heart rate measures [66], which found that individuals with BPD demonstrate less parasympathetic activity in response to emotional films. Greater parasympathetic activity promotes social engagement, whereas less is more indicative of preparedness for fight/flight.…”
Section: Disturbed Controlled and Reflective Processes In Borderlinesupporting
confidence: 93%
“…Low vagal tone has also been reported in patients with various psychiatric disorders (Austin, Riniolo, & Porges, 2007;Friedman, 2007;McCraty, Atkinson, Tomasino, & Stuppy, 2001;Rechlin, Weis, Spitzer, & Kaschka, 1994;Thayer, Friedman, & Borkovec, 1996).…”
Section: Frontal Electroencephalogram (Eeg) Asymmetrymentioning
confidence: 83%
“…Some research examining psychological variables that moderate these differences in vagal tone reactivity is consistent with this possibility. For example, in response to negatively valenced film clips, people with borderline personality disorder showed no change in vagal tone whereas control participants showed an increase in vagal tone (Austin, Riniolo, & Porges, 2007). In response to a mental arithmetic task, people with PTSD showed no change in vagal tone relative to control participants who showed an increase in vagal tone (Sahar, Shalev, & Porges, 2001).…”
Section: Self-esteem and Vagal Tone 16mentioning
confidence: 98%